2018
DOI: 10.1016/j.pharep.2017.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the possible roles of SB-269970 versus ketanserin on carbon tetrachloride-induced liver fibrosis in rats: Oxidative stress/TGF-β 1 -induced HSCs activation pathway

Abstract: Blockade of 5-HT2A and 7 receptors each alone could be a future reliable therapeutic approach in liver fibrosis through a reduction in oxidative stress/TGF-β-induced HSCs activation pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 56 publications
1
5
0
Order By: Relevance
“…Saeid et al treated thermal-injured mice with a 5HTR 2A/2C antagonist (Ketanserin) and found that it could promote anti-fibrotic effects by regulating the phenotype of macrophages [ 77 ]. A study by Atallah et al showed that blocking 5-HTR 2A with Ketanserin or 5-HTR 7 with SB-269970 reduced oxidative stress/TGF-β1-induced liver fibrosis in CCl4-challenged rats [ 78 ], which were consistent with those reported by Dalia et al [ 79 ]. Liang and Shan conducted in vivo and in vitro experiments showing that hyperglycemia or type 2 diabetes can upregulate the expression of 5-HTR 2A , the synthetic enzyme for 5-HT, and MAO-A, leading to increased intracellular 5-HT levels, mitochondrial reactive oxygen species (ROS) generation, and myofibroblastization of HSCs.…”
Section: -Ht In Cirrhosissupporting
confidence: 85%
“…Saeid et al treated thermal-injured mice with a 5HTR 2A/2C antagonist (Ketanserin) and found that it could promote anti-fibrotic effects by regulating the phenotype of macrophages [ 77 ]. A study by Atallah et al showed that blocking 5-HTR 2A with Ketanserin or 5-HTR 7 with SB-269970 reduced oxidative stress/TGF-β1-induced liver fibrosis in CCl4-challenged rats [ 78 ], which were consistent with those reported by Dalia et al [ 79 ]. Liang and Shan conducted in vivo and in vitro experiments showing that hyperglycemia or type 2 diabetes can upregulate the expression of 5-HTR 2A , the synthetic enzyme for 5-HT, and MAO-A, leading to increased intracellular 5-HT levels, mitochondrial reactive oxygen species (ROS) generation, and myofibroblastization of HSCs.…”
Section: -Ht In Cirrhosissupporting
confidence: 85%
“…Serotonin is also known to have numerous functions, such as smooth muscle contraction of blood vessels and bronchi, acceleration of peristaltic movement (Berger et al, 2009), respiratory rhythm (Cinelli et al, 2020), regulation of β cells in the pancreas (Berger et al, 2009;Li et al, 2000), liver regeneration (Inoue et al, 2018;Kamimura et al, 2018), liver fibrosis (Kyritsi et al, 2020), protection against intestinal ischemia (Tackett et al, 2019) and food-seeking behavior (He et al, 2020), and its reuptake inhibitors are used as an antidepressant in relation to gastrointestinal symptoms (Salisbury et al, 2020). In addition, serotonin is reportedly involved in the fibrosis of NAFLD (Atallah et al, 2018), the modification of lipid metabolisms (Namkung et al, 2018), the activation of signal from serotonin receptor on the hepatocytes (Choi et al, 2018), and the modulation of autophagy and Notch signal (Martin et al, 2020). Interestingly, Haub et al (2011) reported that the blockade of the serotonin receptor HTR3, which is the receptor expressed in the intestine, modified the strength of the tight junction and improved the obesity-associated fatty liver in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic fibrosis is characterized by HSC oxidative stress, which may lead to an imbalance in ECM synthesis and degradation and transform HSCs into proliferative myofibroblasts (Kumar et al, 2016; Perepelyuk et al, 2013). One important pathogenic mechanism of HSC activation is oxidative stress, which results in overexpression of various inflammatory cytokines, ultimately resulting in hepatic fibrosis (Atallah et al, 2017; Yin et al, 2013). Chen et al found that EGCG significantly inhibited HSC growth and activation by inducing cell cycle arrest and apoptosis, blocking TGF‐β signal transduction, and inhibiting the gene expression levels of COL1A1 , fibronectin, and α‐SMA (Chen et al, 2002).…”
Section: Discussionmentioning
confidence: 99%